WADY WRODZONECor triatriatum sinister with partially anomalous left pulmonary - Karolczak, Maciej A.; Mądry, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Cor triatriatum sinister is an uncommon congenital intracardiac anomaly resulting from the division of the left atrial chamber by a fibro-muscular membrane. The case report of 12 month girl successfully operated on cor triatriatum sinister with anomalous, strictured connection between left upper pulmonary vein and brachiocephalic vein is presented. Special emphasis is put on a preoperative ultrasound diagnostics.